In Situ Investigation of the Cu/CH3NH3PbI3 Interface in Perovskite Device - Ding, Honghe; Yan, Kangrong; Li, Bairu; Hu, Wanpei; Jia, Lingbo; Zareen, Shah; Freiberger, Marie; Huang, Jianmin; Hu, Jun; Xu, Qian; Li, Yu; Yang, Shangfeng; et al. (Advanced Materials Interfaces, 2021)
In this study, the electronic properties and chemical stability of the Cu/CH3NH3PbI3 interface are investigated in situ by a combination of X-ray photoelectron spectroscopy and synchrotron radiation photoemission spectroscopy (SRPES). The morphology of Cu deposited perovskite surface is monitored by scanning electron microscopy. The results show that the Cu/CH3NH3PbI3 interface is very stable and no chemical reaction between Cu and the perovskite takes place. Moreover, a 0.45 eV interface dipole and a 0.15 eV upward band bending are obtained at the Cu/CH3NH3PbI3 interface. Based on these fundamental findings, a prototype of Cu/CH3NH3PbI3/NiOx/indium tin oxide solar cell device is constructed to check the power conversion efficiency (PCE) and device stability. Although no electron transport material is used in this device, it still exhibits decent performance. The PCE of the device reaches up to 9.99% and remains almost unchanged over a long-time (49 d) storage in a N2-filled glovebox. Through this study it is demonstrated that fundamental understanding of the interfacial structure of a perovskite solar cell is essential in pursuit of rational design of superior perovskite solar cells, and moreover, Cu is a promising electrode candidate for perovskite solar cells.
CRIS-Team Scopus Importer:2021-06-04
Keywords: interfacial structure; long-term storage stability; perovskite solar cells; photoemission spectroscopy; power conversion efficiencies